Managing Crypto as a Business Asset in Prenuptial Agreements/Postnuptial Agreements - Ummul Dwi Andina; Muryanto Lanontji; Andi Muhammad Jafar (International Journal Labs, 2026)
The growth of crypto asset investors in Indonesia will reach 20.9 million by August 2024, but the Marriage Law Number 1 of 1974 has not specifically regulated digital assets, both as joint property and personal property. This research aims to analyze the categorization of crypto assets as business assets that can be regulated through prenuptial and postnuptial agreements to protect the rights of each party. The research approach used is juridical-normative through a literature review of laws, government regulations, academic references, and relevant scientific works. The findings of the study show that crypto assets are grouped into movable objects that do not have a form according to Articles 499 and 503 of the Civil Code, and qualify as business assets because they function as taxable investment instruments. Therefore, the regulation of crypto assets in prenuptial agreements or postnuptial agreements based on Article 35 paragraph (2) jo. Article 29 of the Marriage Law is important to provide legal certainty regarding the status of ownership and division of property.